A Selective Targeting Anchor Strategy Affords Efficient and Stable Ideal‐Bandgap Perovskite Solar Cells. Issue 18 (3rd April 2022) - Liang, Zheng; Xu, Huifen; Zhang, Yong; Liu, Guozhen; Chu, Shenglong; Tao, Yuli; Xu, Xiaoxiao; Xu, Shendong; Zhang, Liying; Chen, Xiaojing; Xu, Baomin; Xiao, Zhengguo; et al.
Abstract: Mixed lead–tin perovskite solar cells (LTPSCs) with an ideal bandgap are demonstrated as a promising candidate to reach higher power conversion efficiency (PCE) than their Pb‐counterparts. Herein, a Br‐free mixed lead–tin perovskite material, FA0.8 MA0.2 Pb0.8 Sn0.2 I3, with a bandgap of 1.33 eV, as a perovskite absorber, is selected. Through density functional theory calculations and optoelectronic techniques, it is demonstrated that both Pb‐ and Sn‐related A‐site vacancies are pushed into deeper energetic depth, causing severe nonradiative recombination. Hence, a selective targeting anchor strategy that employs phenethylammonium iodide and ethylenediamine diiodide as co‐modifiers to selectively anchor with Pb‐ and Sn‐related active sites and passivate bimetallic traps, respectively, is established. Furthermore, the selectivity of the molecular oriented anchor passivation is demonstrated through energetic depth specificity of Pb‐ and Sn‐related traps. As a result, a substantially enhanced open‐circuit voltage ( V OC ) from 0.79 to 0.90 V for the LTPSCs is achieved, yielding a champion PCE of 22.51%, which is the highest PCE among the reported ideal‐bandgap PSCs. The V OC loss is reduced to 0.43 V. Abstract : Aiming for hybrid perovskite solar cells, a novel strategy is developed that using ethylenediamine diiodide and phenethylammonium iodide as co‐modifiers to selectively targeting anchor with lead–tin binary perovskite materials, resulting in comprehensively healing the dual‐sourced defects. As a result, a champion efficiency of 22.51% is achieved, which is the record efficiency among the ideal‐bandgap perovskite solar cells.